2007
DOI: 10.1523/jneurosci.0172-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Robo1 and Robo2 Control the Development of the Lateral Olfactory Tract

Abstract: The development of olfactory bulb projections that form the lateral olfactory tract (LOT) is still poorly understood. It is known that the septum secretes Slit1 and Slit2 which repel olfactory axons in vitro and that in Slit1 Ϫ/Ϫ ;Slit2 Ϫ/Ϫ mutant mice, the LOT is profoundly disrupted. However, the involvement of Slit receptors, the roundabout (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 59 publications
(66 reference statements)
1
42
0
Order By: Relevance
“…Therefore, Robo2 appears to have the strongest repulsive activity in this system, but Robo1 cooperates with Robo2 to prevent crossing. However, the Robo1 knock-out line used here was obtained by gene trap method and may be only be a hypomorphic allele (Long et al, 2004;Fouquet et al, 2007). Accordingly, their telencephalon has a milder phenotype than another line obtained by classic gene targeting method (Andrews et al, 2006;Lopez-Bendito et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, Robo2 appears to have the strongest repulsive activity in this system, but Robo1 cooperates with Robo2 to prevent crossing. However, the Robo1 knock-out line used here was obtained by gene trap method and may be only be a hypomorphic allele (Long et al, 2004;Fouquet et al, 2007). Accordingly, their telencephalon has a milder phenotype than another line obtained by classic gene targeting method (Andrews et al, 2006;Lopez-Bendito et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Slit/Robo signaling controls midline crossing by a variety of axons (Dickson, 2002;Fouquet et al, 2007). In Drosophila, Slit/ Robo signaling also prevents tracheal, sensory precursor cells, and cardiac cells from approaching the midline (Lundstrom et al, 2004;Orgogozo et al, 2004;Santiago-Martinez et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that LOT axons follow a path that is delineated by a specific set of cells, called the LOT cells. It was initially thought that the LOT cells were acting as guidepost cells for LOT axons, but these can be misguided even if the LOT cells are properly positioned, suggesting that these are not sufficient for guiding LOT axons (Fouquet et al 2007). Cell-labeling studies showed that LOT cells are among the first to be born in the dorsal telencephalon and that they migrate tangentially (between E9.5 and E11.5 in the mouse) in a ventral direction to their final position at the surface of the forebrain (Tomioka et al 2000;Kawasaki et al 2006).…”
Section: Semaphorin Function In the Tangential Migration Of Cortical mentioning
confidence: 99%
“…The migration of these cells is directed by Netrin and Sema3F (Kawasaki et al 2006;Ito et al 2008) and the development of the LOT axons depends on the presence of these cells. Slits secreted from the septum, and several secreted semaphorins, also play a key role in LOT positioning (de Castro et al 1999;Nguyen Ba-Charvet et al 1999;Nguyen-Ba-Charvet et al 2002;Fouquet et al 2007). In the telencephalon, several other migratory populations of neurons are implicated in axon guidance.…”
Section: Mechanisms Of Axon Guidance In the Brainmentioning
confidence: 99%